Does War Change Geopolitical Attitudes? A Comparative Analysis of 2014 Surveys in Southeast Ukraine. Issue 3 (3rd May 2020) - O'Loughlin, John; Toal, Gerard
Abstract : In 2014, Ukraine descended into war. The geographically delimited nature of the war in Ukraine, confined to two eastern oblasts, raises the questions of whether war changes geopolitical attitudes in regions proximate to the fighting. Using attitudinal surveys with similar questions in April and December 2014 in the contested territory of southeastern Ukraine three possible effects--that war polarizes populations along national lines, that war rallies the majority to a patriotic cause, and that war induces strategic hedging among non-core nationality populations in government-controlled regions—are examined and generally supported by the survey results.